2015
DOI: 10.4314/tjpr.v14i9.7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Berberine on Zeste Homolog 2 (Ezh2) Enhancement in Human Esophageal Cell Lines

Abstract: Purpose: To investigate the inhibitory effect of berberine treatment on enhancement of zeste of homolog 2 (Ezh2) expressions in KYSE450 human esophageal cancer cells.Methods: Transwell motility chambers were used to analyze cell migration and invasion. Bio-Rad protein assay was used for the determination of protein concentration. Chemiluminescence with ECL system was employed for the detection of protein bands as per the manufacturer’s protocol. Staining was carried out with Alexa-Fluor 647 mouse anti-BrdU ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…BBR also induced inhibition of zeste of homolog 2 (EZH2) expressions in KYSE450, thus preventing cell proliferation by G1‐phase cell cycle arrest and decreasing the invasive tendency of KYSE450 cells. The results of this study showed that BBR exerted an effect on transcriptional reduction of the AXL receptor kinase …”
Section: Effect Of Bbr On Gastrointestinal Carcinomasmentioning
confidence: 67%
See 1 more Smart Citation
“…BBR also induced inhibition of zeste of homolog 2 (EZH2) expressions in KYSE450, thus preventing cell proliferation by G1‐phase cell cycle arrest and decreasing the invasive tendency of KYSE450 cells. The results of this study showed that BBR exerted an effect on transcriptional reduction of the AXL receptor kinase …”
Section: Effect Of Bbr On Gastrointestinal Carcinomasmentioning
confidence: 67%
“…The results of this study showed that BBR exerted an effect on transcriptional reduction of the AXL receptor kinase. 50,83 Finally, BBR exerted an anti-cachectic effect in a colon cancer-bearing mouse model. 82…”
Section: Gastrointestinal Carcinomasmentioning
confidence: 99%